Fishing Season of Large Pelagic Fish in Lempasing Coastal Fishing Port Lampung Province - Setia Agustina; Ririn Irnawati; Adi Susanto (Jurnal Perikanan dan Kelautan, 2016)
Large pelagic fish is one of a major fish that were caught by fishermen inLempasing Coastal Fishing Port. The large pelagic fish, landed in LempasingCoastal Fishing Port, are little tuna, king mackerel, great barracuda, needle fish,and trevally. The purpose of this study was to determine the level of productivityof large pelagic fish and to predicts large pelagic fishing season in LempasingCoastal Fishing Port. The study was conducted in March-July 2015. The methodwas descriptive method. The results showed that the level of productivity of largepelagic fish in Lempasing Coastal Fishing Port tend to fluctuate each year. Thehighest productivity occurred in 2010 amounted to 30.67 kg/trip and lowestproductivity occurred in 2011 amounted to 12.96 kg/trip. The peak fishing seasonof little tuna occur in August with index value 176.76%. The peak fishing seasonof king mackerel occur in Mei with index value 176.93%. The peak fishing seasonof great barracuda occur in March with index value 136.14%. The peak fishingseason of needle fish occur in December with index value 184.54%. The peakfishing season of trevally occur in December with index value 156.54%.